Estudo de características ópticas de materiais obtidos via sol-gel - Nelicio Faria de Sales (2004)
The goal of this work was to study the influence of concentration and temperature of reagents on structural properties of sol-gel silica xerogels doped with copper nitrate and cobalt nitrate obtained by sol-gel methodology and to characterize them in aiming future optical applications. The samples were prepared by hydrolysis and condensation of (TEOS) in alcohol (ethanol) and deionized water. Three samples were doped with copper nitrate (Cu(NO3)2.3H2O) and cobalt nitrate (Co(NO3).6H2O), in the crescent molar ratios of TEOS/dopant of 0.0085, 0.0425 and 0.085 and 0.007, 0.035 and 0.07, respectively. As catalyst we used nitric acid and the initial pH of sols during the synthesis was 1.5. As additive we used formamide in the crescent molar ratios ofTEOS/formamide of 0.0013, 0.038 and 0.064. The samples were always grouped and treated in the same way. Different densities were obtained and it was possible to observe the differences between the basic and doped samples. Using Fourier transform infrared spectroscopy (FTIR) it was possible analyze the absorption peaks of the principal bonds of Si-O and Si-O(H). Using visible-near infrared spectroscopy it was possible to verify the characteristic filter color of the samples and the visible windowwas measured for each sample. The structural properties obtained by helium picnometry, the porosity evaluated by nitrogen gas adsorption and the refractive index (n), were used to evaluate the final refractivity of samples. The gap energy Eg was then estimated and presented in an Eg x n graphic.